Misregulation of sex-lethal and disruption of male-specific lethal complex localization in Drosophila species hybrids. - Pal Bhadra, M.; Bhadra, U.; Birchler, J.A. (Genetics, 2006)
A major model system for the study of evolutionary divergence between closely related species has been the unisexual lethality resulting from reciprocal crosses of Drosophila melanogaster and D. simulans. Sex-lethal (Sxl), a critical gene for sex determination, is misregulated in these hybrids. In hybrid males from D. melanogaster mothers, there is an abnormal expression of Sxl and a failure of localization of the male-specific lethal (MSL) complex to the X chromosome, which causes changes in gene expression. Introduction of a Sxl mutation into this hybrid genotype will allow expression of the MSL complex but there is no sequestration to the X chromosome. Lethal hybrid rescue (Lhr), which allows hybrid males from this cross to survive, corrects the SXL and MSL defects. The reciprocal cross of D. simulans mothers by D. melanogaster males exhibits underexpression of Sxl in embryos.